A responsive evaluation approach in evaluating the safe schools and the child-friendly schools programmes in the Limpopo province - Mabasa, Layane Thomas (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.